ON THE TYPES OF NARRATIVE AND NARRATIVE IN THE PRIMARY CLASSROOM - Kunduzoy ATAMURODOVA (Scholar Express Journal, 2024)
In the process of primary education, the importance of writing and retelling is so great that it is necessary to pay attention to the important aspects when choosing a statement on various topics in order to develop the written speech of each student. That's why the main focus of the textbooks is that they are fully compatible with the requirements of today's era. In order to educate elementary school students to be comprehensively prepared for creative and written speech, and most importantly, the correct formation of connected speech components of retelling and narration in them is effectively used in primary education. In this article, information is given about the presentation and its types conducted in primary classes, the types of presentation in the primary class mother tongue classes, appropriateness of the purpose, and the basis for the development of students' abilities. Detailed ideas about the receiver components are given
Keywords: Statement; types of statement; connected speech